The potential influence of stochastic resonance vibrations on neuromuscular strategies and center of pressure sway during single-leg stance - Chen, Wen-Ming; Li, Jie-Wen; Geng, Xiang; Wang, Chen; Chen, Li; Ma, Xin (Clinical biomechanics (Bristol), 2020)
Stochastic resonance vibrations are known to enhance balance in the elderly and patients with impaired plantar sensation. However, the underlying mechanisms of plantar vibrations on balance capacity are not well resolved. This study investigated the impact of stochastic resonance vibrations on activities of major extrinsic foot muscles and center of pressure sway in tactile inhibited subjects. Using a customized vibration insole, single-leg stance tests were performed in fourteen healthy subjects at control, ice-intervention-only (inhibited foot sensation) and ice-intervention plus vibration conditions. The sway parameters and the root mean square of electromyography of medial gastrocnemius, tibialis anterior, peroneus longus, and extensor digitorum longus were examined. The sway area in the ice-intervention-only condition was significantly increased compared with the control (P < .001). Following vibrations, the sway area, however, was significantly decreased. Regression analysis showed the activity levels of all extrinsic foot muscles were positively correlated with sway area when foot sensation was inhibited. In contrast, following vibrations, only that of the tibialis anterior muscle was positively correlated with sway area, indicative of a muscle control strategy similar to the control condition. The study showed that stochastic resonance vibrations could effectively reduce body sway in the healthy subjects with inhibited foot sensation. The effects seemed to be associated with improved muscle activities in particular to the tibialis anterior muscle. It suggested that vibration insole may be used as a means to affect neuromuscular strategies to enhance balance control in people with diminished plantar sensations. •Muscle activities due to stochastic resonance vibrations are investigated.•Foot muscle activities increase with plantar sensation inhibited.•Vibration insole affects neuromuscular strategies for balance control.